2012
DOI: 10.1024/1010-0652/a000074
|View full text |Cite
|
Sign up to set email alerts
|

Berufliche Interessensorientierungen und kognitive Leistungsprofile von Lehramtsstudierenden mit unterschiedlichen Fachkombinationen

Abstract: Im Hinblick auf professionelle Entwicklungsprozesse von Lehramtsstudierenden beschäftigen sich aktuelle Forschungsarbeiten mit der Analyse personaler Studieneingangsvoraussetzungen und ihrer prognostischen Validität für verschiedene Erfolgsmaße. In der vorliegenden Studie wurde an einer Stichprobe von 227 Lehramtsstudierenden geprüft, inwiefern sich in Abhängigkeit der gewählten Fachkombinationen unterschiedliche Profile berufsbezogener Interessensstrukturen und kognitiver Leistungsfähigkeit sowie erfolgsrelev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 25 publications
2
28
0
7
Order By: Relevance
“…The sample investigated in this study was part of the second panel wave of the Study on Individual and Organizational Influences on Study Performance in Teacher Education (SioS; Kaub et al, 2012;Reichl, Wach, Spinath, Brünken & Karbach, 2014;Ruffing et al, 2014). This German research project aims to investigate professional competencies in teacher education and therefore runs a longitudinal assessment over 6 years also administering a control group of psychology students.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…The sample investigated in this study was part of the second panel wave of the Study on Individual and Organizational Influences on Study Performance in Teacher Education (SioS; Kaub et al, 2012;Reichl, Wach, Spinath, Brünken & Karbach, 2014;Ruffing et al, 2014). This German research project aims to investigate professional competencies in teacher education and therefore runs a longitudinal assessment over 6 years also administering a control group of psychology students.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…A large number of studies examined the significance of different motivational constructs for students' SAS. For instance, a study by Kaub et al (2012) demonstrated the relevance of students' vocational interests for their level of SAS. Moreover, students expressing a rather intrinsic motivation for choosing a certain major were also more satisfied with their academic studies, whereas extrinsic motivation was not associated with SAS (Künsting and Lipowsky, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Päßler, Hell und Schuler (2011) weisen darauf hin, dass kognitive Merkmale für die Studien-und Berufsbewährung bei Lehrkräften relevant sind. Die Bedeutsamkeit von kognitiven Merkmalen für Lehrkräfte zeigt sich bereits beim Studienerfolg (Kaub et al, 2012;Krammer, 2014). Zusätzlich ist das Fachwissen der Lehrkräfte eine notwendige, wenn auch nicht hinreichende, Voraussetzung für eine hohe Qualität des Unterrichts (Baumert & Kunter, 2011).…”
Section: Theoretischer Hintergrundunclassified
“…Emotionale Stabilität, Extraversion und Gewissenhaftigkeit haben sich als relevant für die Bewährung im Lehramtsstudium und Lehrerberuf gezeigt . Auch berufliches Interesse steht in Zusammenhang mit dem Studienerfolg (Hanfstingl & Mayr, 2007;Kaub et al, 2012). Demnach ist es nicht zielführend, künftige Lehrkräfte nur aufgrund von kognitiven Leistungstests auszuwählen.…”
Section: Theoretischer Hintergrundunclassified